Comparative genetics in the grasses - Gale, Michael D. (The National Academy of Sciences, 1998)
Genetic mapping of wheat, maize, and rice and other grass species with common DNA probes has revealed remarkable conservation of gene content and gene order over the 60 million years of radiation of Poaceae. The linear organization of genes in some nine different genomes differing in basic chromosome number from 5 to 12 and nuclear DNA amount from 400 to 6,000 Mb, can be described in terms of only 25 “rice linkage blocks.” The extent to which this intergenomic colinearity is confounded at the micro level by gene duplication and micro-rearrangements is still an open question. Nevertheless, it is clear that the elucidation of the organization of the economically important grasses with larger genomes, such as maize (2n = 10, 4,500 Mb DNA), will, to a greater or lesser extent, be predicted from sequence analysis of smaller genomes such as rice, with only 400 Mb, which in turn may be greatly aided by knowledge of the entire sequence of Arabidopsis, which may be available as soon as the turn of the century. Comparative genetics will provide the key to unlock the genomic secrets of crop plants with bigger genomes than Homo sapiens.